Collaboration and themes in the Journal for Language Teaching (2001–2023): A network analysis - Senekal, Burgert; Du Plessis, Theo (Journal for Language Teaching, 2024)
This study provides a quantitative overview of the Journal for Language Teaching from 2001 to 2023. More specifically, the current study applies network science to study both the co-authorship network and to identify topics. In addition, the journal’s focus on multilingualism is investigated. The results indicate a notable growth in collaborative research in the journal, shown by the increasing average number of authors per paper. The analysis of the co-authorship network reveals a moderately connected network, with a significant group of authors forming the giant component. Important authors are also recognised based on centrality measures, highlighting their crucial roles in fostering connections within the network. Collaboration primarily happens within universities, but when it extends across institutions, inland universities tend to collaborate more frequently than those on the coast or between coastal and inland universities. Furthermore, the analysis of research topics identified eight distinct themes prevalent in the Journal for Language Teaching, encom-passing various areas in language education. It is also shown that both in the language of papers and in their language focus, the journal foregrounds English throughout this period, and papers tend to be more often in English and focus on English in recent years.